Multi-Class Ovarian Cancer Subtype Classification in Histopathological Images Using Swin Transformer - P. Costa, Juliany; B. Estrela, Igor R.; de Carvalho Filho, Antônio O.; C. Paiva, Anselmo; C. Silva, Aristófanes; Diniz, João O. B. (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2025)
Ovarian cancer has a high mortality rate due to late diagnosis, which drives ongoing research to improve histopathological image analysis through artificial intelligence (AI). This study proposes a method for the automatic classification of four ovarian cancer subtypes using the Ovarian Cancer and Subtypes Histopathology Dataset, incorporating image processing techniques, data augmentation, and deep learning. The best performance was achieved with the Swin Transformer architecture, reaching an average accuracy of 98%. These results suggest that the proposed method is a promising approach for classifying ovarian cancer subtypes in histopathological images.